The predictive ability of the 313 variant-based polygenic risk score for contralateral breast cancer risk prediction in women of European ancestry with a heterozygous BRCA1 or BRCA2 pathogenic variant - Lakeman, Inge M M; van den Broek, Alexandra J; Vos, Juliën A M; Barnes, Daniel R; Adlard, Julian; Andrulis, Irene L; Arason, Adalgeir; Arnold, Norbert; Arun, Banu K; Balmaña, Judith; Barrowdale, Daniel; Benitez, Javier; et al. (Genetics in medicine, 2021)
PURPOSE: To evaluate the association between a previously published 313 variant-based breast cancer (BC) polygenic risk score (PRS313) and contralateral breast cancer (CBC) risk, in BRCA1 and BRCA2 pathogenic variant heterozygotes. METHODS: We included women of European ancestry with a prevalent first primary invasive BC (BRCA1 = 6,591 with 1,402 prevalent CBC cases; BRCA2 = 4,208 with 647 prevalent CBC cases) from the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA), a large international retrospective series. Cox regression analysis was performed to assess the association between overall and ER-specific PRS313 and CBC risk. RESULTS: For BRCA1 heterozygotes the estrogen receptor (ER)-negative PRS313 showed the largest association with CBC risk, hazard ratio (HR) per SD = 1.12, 95% confidence interval (CI) (1.06-1.18), C-index = 0.53; for BRCA2 heterozygotes, this was the ER-positive PRS313, HR = 1.15, 95% CI (1.07-1.25), C-index = 0.57. Adjusting for family history, age at diagnosis, treatment, or pathological characteristics for the first BC did not change association effect sizes. For women developing first BC < age 40 years, the cumulative PRS313 5th and 95th percentile 10-year CBC risks were 22% and 32% for BRCA1 and 13% and 23% for BRCA2 heterozygotes, respectively. CONCLUSION: The PRS313 can be used to refine individual CBC risks for BRCA1/2 heterozygotes of European ancestry, however the PRS313 needs to be considered in the context of a multifactorial risk model to evaluate whether it might influence clinical decision-making.
Keywords: rizikové faktory; lidé; retrospektivní studie; BRCA2 Protein; Genetic Predisposition to Disease; Risk Factors; Humans; Breast Neoplasms; Heterozygote; Retrospective Studies; BRCA1 Protein; ženské pohlaví; genetická predispozice k nemoci; mutace; protein BRCA2; Female; protein BRCA1; heterozygot; nádory prsu; dospělí; Adult; Mutation